The preterm microbiome in UK infants exposed to modern intensive care infection control practices. (7th June 2011) - Perry, J; Embleton, N; Narayanan, M; Kerr, J; Marrs, E; Migorrian, S; Berrington, J
Abstract : Background: The importance of the microbiome to the health of preterm infants is increasingly recognised. Much of the data on microbiome development in preterm infants is from 15–30 years ago: infants, nursery practices, infection control measures and antibiotic use are now very different. Objective: To describe gut colonisation in modern preterm infants (<32 weeks) in comparison to existing data and explore differences in infants developing necrotising enterocolitis (NEC). Methods: The first stool, and weekly stool was collected as routine surveillance from birth to 8 weeks. A standard operating procedure was developed to identify the maximum numbers of species and strains of organisms present by standard culture. Results: 100 stools came from 38 infants, median gestational age 27 weeks (23–32 weeks), birth weight 895 g (520–1850 g). 35 received breast milk, 29 received fluconazole prophylaxis. Stools grew a median of three separately identifiable species/strains of organisms (range 0–8). The commonest organism was CONS (40% of stools, 55% of babies). Only six infants were ever colonised with lactobacilli, 1 with bifidobacteria and none with fungi. Eight infants had NEC (4 surgical). Those with NEC had more Enterococci (75% vs 23%) and Klebsiella (62% vs 32%). Conclusions: Compared to historical data we identified less species diversity, more colonisation with coagulase negative staphylococci, less lacto- and bifidobacteria, and no fungi. Infants developing NEC had different colonisation patterns. Current exposures on NICU result in a significantly abnormal microbiome and may predispose to NEC.